WOMEN ENTREPRENEURS IN TOURISM WITIN THE MORAVICA DISTRICT - Munitlak Ivanović, Olja; Mijatov, Maja; Đeri, Lukrecija; Tomašević, Ema (Turizam, 2022)
The research was focused on analyzing the role of women entrepreneurs in business sector of tourism within the Moravica District, or more precisely the focus was on the experience and challenges of women entrepreneurs within the researched territory. The research results indicated to reliable insight into the current position, as well as possibilities and threats of further tourism development, by considering concrete advantages and difficulties that might occur on the basis of starting their own business, especially in the case of women entrepreneurs. In respect to that, the research results provided a realistic perception of opportunities, as well as barriers for further development of women entrepreneurship in tourism of the Moravica District. The research results pointed to the fact that women from the Moravica District, who are independently engaged in tourism, are faced with various challenges. These challenges mainly occurred by the absence of appropriate trainings and educations in tourism industry, as well as by insufficient access to financial resources for starting or improving their business. All together might provide a basis for organization of educations and trainings that will obtain all the necessary information on different subventions that might facilitate the business operations of female entrepreneurs.
Keywords: women entrepreneurs; entrepreneurship; start-up business; tourism; Moravica District